Detection of SARS-CoV-2 BA.2.86 by lateral flow devices - Abbie Bown; Angela Sweed; Matthew Catton; Joshua Nelthorpe-Cowne; Hermione Conti-Frith; Ruth Elderfield; Jacob Terrey; Hamsa Abib; Caleb Lui; Ella Fisher; Kevin R. Bewley; Naomi S. Coombes; et al. (International Journal of Infectious Diseases, 2024)
We evaluated the performance of 12 lateral flow devices by assessing their analytical sensitivity for SARS-CoV-2 variant BA.2.86. Kits from ACON, Orient Gene, Xiamen Biotime, Getein, and SureScreen detected variant BA.2.86 to sufficient sensitivity levels, comparable to those observed with previous Omicron variants. The stocks of lateral flow devices currently held by the UK government do not currently need changing for deployment for this variant.